Screening of lignin-degrading fungi for their ability to decay cassava residue - Bin Xu; Huixing Li; Chaojun Du; Ying Wang; Bin Li (Functional Materials, 2016)
To screen applicable fungi for their ability to decay cassava residue, nineteen lignin-degrading fungi were isolated by guaiacol and azure B plates. Cassava residue decayed characteristics of the isolates were evaluated systematically by principal component analysis (PCA) of weight and components loss data, and compared with those of Phanerochaete chrysosporium and Trametes sp. SYBC-L4. Four groups of decayed cassava residue were identified. Fungus N1 and N3 grouped together and showed high lignin-degrading selectivity. Fungus N5 and N8 grouped with P. chrysosporium and showed high degradation ability. During the four weeks incubation, the lignin-degrading selectivity value of fungus N3 ranged from 1.14 to 1.38 and was the best, the weight loss of fungus N5 and N8 achieved 30.93% and 33.34%, respectively. Fungus N3, N5, and N8 were identified as Pleurotus sp., Trametes sp. and Coriolopsis sp. based on 18S rDNA gene sequences, respectively. PCA is an effective method in recognizing cassava residue decayed characteristics of fungi and is helpful to screen fungi for their potential application. The three screened out fungi could be used to decay cassava residue for enhancement of its bioconversion efficiency.